(untitled) (Journal of Economic Research & Business Administration, 2015)
In article parameters of system of measurement of the index of global competitiveness (IGC) which in total provide efficiency of development and competitiveness of the country are analyzed. On the basis of this analysis levels of increase of competitiveness on stages of development of economy are concretized. Depending on extent of influence and the accounting of importance of each of 12 components of IGK they are grouped in subindexes and stages of development of economy. Weight shares of each subindex at a certain stage of development are specified. According to the qualifier of development of the countries of the world, the place of Kazakhstan is shown. For it depending on goals subindexes on which it is required to make efforts for lag overcoming from other countries are concretized. On the other hand, the analysis of measuring instruments of development and global competitiveness gives the chance to another developing to estimate the countries the opportunities and to create strategy of future development on achievement of high level in global competitiveness.